APPROACH TO DETECTING ERRORS AND RESTORING THE CORRECT FUNCTIONING OF SOFTWARE IN MODERN CONTROL SYSTEMS IMPLEMENTED ACCORDING TO THE PRINCIPLE "SYSTEM ON A CRYSTAL" - Shtanenko, Serhii; Samokhvalov, Yurii; Tolyupa, Serhii (Science-based technologies, 2023)
The article analyzes the existing mathematical models of software reliability of modern control systems, reveals the advantages and disadvantages. The presented mathematical models make it possible to evaluate the characteristics of errors in programs and predict their reliability during engineering and maintenance. These models are probabilistic themselves, and the forecasts’ reliability depends on the accuracy of the initial data and the depth of forecasting over time. Methods are considered as providing and improving the reliability of software tools for computing systems that implement the "system on a chip" principle. The implementation of these methods of providing and improving reliability will enable modern computing systems to maintain the ability to fulfill the rules of information processing specified by the specification in real operating conditions for the required time interval in a proper way. A plan for restoring the correct functioning of software tools is proposed, which is based on a scheme for constructing multi-step solutions based on logical-linguistic models and ideas of the theory of artificial intelligence. In particular, one of these methods is the method of situational control, which is based on the representation of knowledge about the control object and how to control this object. In addition, logical-linguistic models implement their own specific methods for finding optimal solutions, focused on a qualitative description of the components of the solutions, the relationships between them and the criteria for choosing a solution. At the same time, situational management systems are not designed to optimize the management process itself, they are focused only on such management, in which the results will be identical to those that a person receives, and in some cases even better. The implementation of the proposed plan, which is based on the method of situational management, will make it possible to build a deductive procedure for restoring the correct functioning of software, and this, in turn, will allow a modern computer system to adapt both to negative situations and to intentional or unintentional adverse effects.